BENEFITS OF THERAPY IN TASAWUF TO OVERCOME SPIRITUAL PROBLEMS IN THE MELLENNIAL ERA - Imran, Zulfi; Syarifuddin, Syarifuddin (Proceeding International Seminar of Islamic Studies, 2024)
The benefits of therapy in overcoming spiritual problems experienced by Muslims in the millennial era is a study that is said to be going viral. The occurrence of spiritual problems stems from the loss of Godly values caused by Muslims themselves, who are always moving further and further away from the center of existence. For this reason, there is no better alternative in responding to the spiritual problem that has given rise to various spiritual illnesses today, except that millennial humans must return to the center of existence. The basic assumption about humans consisting of physical and spiritual aspects, material and spiritual, is a complete dimension that can be an alternative for millennial humans to overcome spiritual illnesses. The two actually go hand in hand, complementing each other. Through the spiritual dimension, humans are required to return to the center of existence through iktikaf in the mosque or also looking for a teacher whose spirit reaches the Prophet, so that in this iktikaf we get guidance that can cleanse the soul which, if done with sincerity, the heart is capable of musyahadah (witnessing) and ma'rifah (knowing everything that is not visible. From the external side, knowledge of Sufism is part of self-enlightenment which must be done with effort, serious effort towards the spiritual aspect.